Investing in Mini Grids Now, Integrating with the Main Grid Later : A Menu of Good Policy and Regulatory Option - World Bank Group (World Bank, Washington, DC, 2019)
Mini grids can economically supply electricity to people in areas that the main grid is unlikely to reach soon. Mini grids can be quickly deployed and are increasingly price-competitive against traditional sources of energy. They can attract private financing and operate without subsidies when allowed to charge cost-recovery tariffs. Moreover, the arrival of the main grid does not mean that the investment in mini grids will be wasted: their generation and distribution assets can generally be reused in an integrated system. The key is to define—in advance—technical standards and commercial options for integration once the main grid arrives.